A furazolidone-based quadruple therapy for Helicobacter pylori retreatment in patients with peptic ulcer disease (Clinics, 2005)
PURPOSE: Many of the currently used eradication regimens against Helicobacter pylori fail to cure the infection either due to antimicrobial resistance or to poor patient compliance. The infection leads to increased risk of developing potentially severe complications, such as gastric cancer. This study was aimed at assessing the efficacy and safety of a quadruple therapy with furazolidone for H. pylori retreatment. METHODS: Patients who had failed one or more eradication regimens against H. pylori infection underwent upper gastrointestinal endoscopy. Biopsy specimens were taken from the gastric antrum and corpus for histology and for a urease test and. Patients received omeprazole 20 mg, bismuth citrate 240 mg, tetracycline 500 mg, and furazolidone 200 mg, all twice daily for 7 days. Therapeutic success was evaluated by endoscopy and biopsies 8 weeks after the end of treatment. RESULTS: Sixty two patients were enrolled, and 58 completed the study. Under this protocol, H. pylori eradication was achieved in 39/58 patients (67%). Mild adverse events were reported. CONCLUSION: The short quadruple therapy course with furazolidone is well tolerated, inexpensive, and effective in retreatment for H. pylori infection. It is a good option for developing countries.